(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Cytokines are small proteins that mediate and regulate immunity. They are involved in the pathogenesis of many diseases including cancers. The concentration of these proteins in biological fluids (serum or plasma) and tissues in diseases may suggest pathway activation that leads to inflammatory response or disease progression. Therefore, these cytokines may be useful as a tool for screening, diagnosis classification between stages of disease or surveillance for therapy. Enzyme-linked immunosorbent assays (ELISA) and bioassay have been used as a gold standard in cytokine level measurements in clinical practice. However, these methods allow only single cytokine detection at a time and ineffective for screening purposes. Hence, the innovation of multiplexing technology allows measurement of many of these soluble proteins simultaneously, thus allowing rapid, cost-effective and better efficiency by using a minute amount of sample. In this study, we explored the profiles of key inflammatory cytokines from the serum derived from diffuse large b-cell lymphoma (DLBCL, n =11) and healthy volunteers (N, n =11) using multiplexed bead-based immunoassays. We aimed to evaluate if the levels of these cytokines are significantly different in these two groups and explore the possible application of the cytokine as biomarkers in early-stage screening and/or surveillance. Our results show a significantly high level of IL-17A, IL-10 and IL-6 in DLBCL-derived serum compared to n-derived serum. These preliminary results were obtained from a small sample size and could be further validated with a larger sample size cohort to produce a panel of biomarkers for DLBCL. Our findings might be useful in developing a disease-specific panel for biomarker screening assay. This could be used for early diagnosis and/or treatment surveillance.